Assessing the Individual, Neighborhood, and Policy Predictors of Disparities in Mental Health Care. (August 2017) - Cook, Benjamin L.; Zuvekas, Samuel H.; Chen, Jie; Progovac, Ana; Lincoln, Alisa K.
This study assesses individual- and area-level predictors of racial/ethnic disparities in mental health care episodes for adults with psychiatric illness. Multilevel regression models are estimated using data from the Medical Expenditure Panel Surveys linked to area-level data sets. Compared with Whites, Blacks and Latinos live in neighborhoods with higher minority density, lower average education, and greater specialist mental health provider density, all of which predict lesser mental health care initiation. Neighborhood-level variables do not have differential effects on mental health care by race/ethnicity. Racial/ethnic disparities arise because minorities are more likely to live in neighborhoods where treatment initiation is low, rather than because of a differential influence of neighborhood disadvantage on treatment initiation for minorities compared with Whites. Low rates of initiation in neighborhoods with a high density of specialists suggest that interventions to increase mental health care specialists, without a focus on treating racial/ethnic minorities, may not reduce access disparities.